(3TQM aUd aj BNQ GdebGdI GdKGfjI ef cJGH CQSWh GdHQgGf hEUdGM NWC ajgs - (3fLe GdOjf CHh GdaJhM CMeO Hf eMeO Hf GdSQj hcGf jYQa HGHf GdUdGM,J (B548 (3g` s
(3ChdgG (B:s
(3bGd CQSWh WGdjS ai BNQ GdebGdI GdKGfjI ef cJGHg ai GdHQgGf Jfbd Edi HTQ eJi Hf jhfS GdYfGfi jYfi Cf GdYdh hgj GdMO GdChSW ai GdbjGS s
(3BNQgG (B:s
(3Cf jYde EPG de jHbi TF BNQ gh YdI dgPG aCfG EPG YdefG Cf GdNGQLI eJSGhjI dRhGjG CQHY Je GdTQM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHY YTQs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs